2014
DOI: 10.1037/per0000070
|View full text |Cite
|
Sign up to set email alerts
|

Prospective associations between features of borderline personality disorder, emotion dysregulation, and aggression.

Abstract: Difficulties with emotion regulation and behavioral instability, including impulsive aggression, are seen as core dimensions underlying borderline personality disorder (BPD). Although both BPD and antisocial personality disorder (ASPD) are associated with impulsivity and aggressive behavior, difficulties regulating emotions may be associated uniquely with BPD and may explain distinctive associations between BPD and aggression. This study was designed to examine the unique prospective associations between BPD s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
2
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 54 publications
(79 reference statements)
9
101
2
6
Order By: Relevance
“…Sebaliknya, siswa yang memiliki kemampuan mengelola emosi yang rendah akan cenderung kesulitan meregulasi emosi untuk meminimalisir munculnya perilaku agresi, sehingga regulasi emosi menjadi salah satu unsur penting bagi siswa untuk memunculkan atau meminimalisir perilaku agresi. Hal ini dikarenakan regulasi emosi memiliki pengaruh yang lebih besar terhadap perilaku agresi (Garofalo, Holden, Zeigler-Hill, & Velotti, 2016;Roberton, Daffern, & Bucks, 2012;Scott, Stepp, & Pilkonis, 2014).…”
Section: Pembahasan Tingkat Agresi Berdasarkan Jenis Kelaminunclassified
“…Sebaliknya, siswa yang memiliki kemampuan mengelola emosi yang rendah akan cenderung kesulitan meregulasi emosi untuk meminimalisir munculnya perilaku agresi, sehingga regulasi emosi menjadi salah satu unsur penting bagi siswa untuk memunculkan atau meminimalisir perilaku agresi. Hal ini dikarenakan regulasi emosi memiliki pengaruh yang lebih besar terhadap perilaku agresi (Garofalo, Holden, Zeigler-Hill, & Velotti, 2016;Roberton, Daffern, & Bucks, 2012;Scott, Stepp, & Pilkonis, 2014).…”
Section: Pembahasan Tingkat Agresi Berdasarkan Jenis Kelaminunclassified
“…BPD patients often use dysfunctional, nonmentalistic strategies (Bateman & Fonagy, 2004) in order to regulate unpleasant emotional states and psychological suffering, such as self-injury or substance abuse (Linehan, 1993;Scott, Stepp, & Pilkonis, 2014). This can be described as poor metacognitive mastery and can be demonstrated by low levels on the Mastery subscale of the MAS-R .…”
Section: Metacognition In Borderline Personality Disordermentioning
confidence: 99%
“…Additionally, some studies have reported that individuals with cluster B PDs exhibit greater inability to modulate emotional expression or maintain suitable behavior in the presence of intense negative affect, 34,35 characteristics that have not been described for clusters A and C. This difficulty in emotional adjustment may lead to SB as well as to problems in the workplace. Thus, our results are consistent with other studies that have shown an association between SA and lack of a paid occupation.…”
Section: Discussionmentioning
confidence: 99%